Challenges and Opportunities for Implementing IFRS Standards Globally - Misrofingah Misrofingah; Ela Widasari; Rudiyanto Rudiyanto; Hanifah Hanifah; Herlina Herlina (Yayasan Adra Karima Hubbi, 2024)
Globally, the implementation of International Financial Reporting Standards (IFRS) offers many opportunities and challenges. Although IFRS standards aim to increase transparency and consistency in financial reporting worldwide, their implementation faces many challenges. One of the main challenges is differences in existing national accounting systems, which often require major adjustments to meet IFRS standards. Infrastructure and training readiness are additional issues. Many businesses, especially in developing countries, face difficulties in adopting the necessary technology and training staff to comply with IFRS standards. However, opportunities to improve the quality of financial reporting also arise as a result of implementing IFRS. To increase the credibility of financial reports and make it easier to compare company performance around the world, IFRS standards provide a more standardized and transparent framework. In addition, IFRS adoption can encourage regulatory harmonization and increase market efficiency by reducing differences in financial reporting between countries. Overall, although there are significant obstacles to the global adoption of IFRS standards, the benefits of transparency, credibility and market efficiency that they offer cannot be ignored.